Pharmaceutical Cold Chain Logistics Optimization Considering Access‐Related Upstream Conditions: A Government–Enterprise Cogovernance Perspective. - Zhong, Limengtao; Liang, Xuedong; Dai, Yujie; Wang, Wenju; Chao, Xiangrui; Chen, Qing-Wei (Health & Social Care in the Community, 2026)
Pharmaceutical cold chain logistics plays a key role in shaping upstream supply chain conditions that may be indirectly associated with community access to medicines. It is energy‐intensive and operationally complex, requiring trade‐offs among emissions reduction, delivery reliability, product integrity and logistics costs within a policy‐enforced sustainable environment. However, existing studies largely treat policy implementation and enterprise logistics responses in isolation, leaving the interaction between upper level government instruments and lower level operational decisions, and their impact on these system‐level outcomes underexplored. To address this issue, we first develop a bilevel robust optimisation model under a government–enterprise cogovernance framework to characterise interactions between environmental policy instruments and enterprise multimodal transport routing decisions in pharmaceutical cold chain logistics under temporal uncertainty. Within this framework, four logistics‐side proxy variables inspired by the 4A framework (availability, accessibility, acceptability, affordability) are introduced to represent logistics‐mediated system conditions potentially associated with medicines access (LMCA), rather than direct measures of access outcomes. For computational tractability, the bilevel structure is reformulated into a single‐stage fuzzy compromise model, enabling direct derivation of compromise solutions under different governance preferences without requiring the solution of a strict Stackelberg equilibrium problem. A case study along the Chengdu–Shanghai pharmaceutical corridor illustrates that the influence of carbon taxation and multimodal transport subsidies on system outcomes depends on decision‐maker preferences, temperature conditions and model robustness requirements. When enterprise preference is dominant, carbon taxation above a threshold can alter routing behaviour, but under high‐temperature conditions, refrigeration cost dominance weakens policy responsiveness. In the illustrated corridor, subsidies reduce emissions more directly in most cases (e.g., from approximately 5819.00 to 4245.00 kg, a roughly 27.05% reduction at a subsidy multiplier of 3), but at the expense of higher public expenditure. These findings provide a logistics‐based analytical perspective on environmental policy–enterprise interactions and their implications for environmental outcomes and LMCA.